2007
DOI: 10.1007/s10295-007-0267-8
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus buchneri strain NRRL B-30929 converts a concentrated mixture of xylose and glucose into ethanol and other products

Abstract: Lactobacillus buchneri strain NRRL B-30929 was isolated from a fuel ethanol production facility. This heterofermentative, facultative anaerobe can utilize xylose as a sole carbon source and tolerates up to 12% ethanol. Carbohydrate utilization (API, Biomerieux) and Phenotype Microarrays (PM, Biolog) analyses indicated that the strain is able to metabolize a broad spectrum of carbon sources including various monosaccharides (C5 and C6), disaccharides and oligosaccharides, with better rates under anaerobic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 35 publications
0
36
1
4
Order By: Relevance
“…L. buchneri has been previously isolated in matured cheeses, but it was neves defined as the dominant population [25] [35]. It is often used as inoculum in silage, participating in the fermentation process by the production of lactic and acetic acid, allowing the control of unwanted microorganisms [2] [36]. This bacterium has shown a strong antagonist activity against Campylobacter jejuni [7] and produces a bacteriocin capable of inhibit Listeria, Bacillus, Enterococcus, Lactobacillus, Leuconostocs, Micrococcus, Pediococcus and Streptococcus [37].…”
Section: Discussionmentioning
confidence: 99%
“…L. buchneri has been previously isolated in matured cheeses, but it was neves defined as the dominant population [25] [35]. It is often used as inoculum in silage, participating in the fermentation process by the production of lactic and acetic acid, allowing the control of unwanted microorganisms [2] [36]. This bacterium has shown a strong antagonist activity against Campylobacter jejuni [7] and produces a bacteriocin capable of inhibit Listeria, Bacillus, Enterococcus, Lactobacillus, Leuconostocs, Micrococcus, Pediococcus and Streptococcus [37].…”
Section: Discussionmentioning
confidence: 99%
“…Selected species of lactic acid bacteria (LAB) are known as robust, stress tolerant, fermentative organisms that are capable of utilizing a wide range of carbohydrate substrates for production of various products, and thus have potential as microbial catalysts for the production of fuels and chemicals from lignocellulosic biomass. In a previous search for strains capable of metabolizing xylose, the most abundant five‐carbon sugar derived from hemicelluloses, Lactobacillus buchneri strain NRRL B‐30929 was identified for growing rapidly in the presence of high concentrations of xylose . This aerotolerant anaerobe belongs to the heterofermentative LAB and is capable of fermenting mixed glucose, xylose, and other oligosaccharides as well as lignocellulosic biomass hydrolysates into ethanol (EtOH) and other organic acids .…”
Section: Maldi‐ms Identification Of Proteins From L Buchneri B‐30929mentioning
confidence: 99%
“…Whereas repression of pentose metabolism by glucose is a well-known phenomenon, some exceptional microorganisms including Lactobacillus brevis [45], Lactobacillus buchneri [46] and Clostridium thermohydrosulfuricum [47] exhibit simultaneous utilization of mixed sugars. Proteomic analysis of L. brevis has revealed that protein levels of XylA and XylB are reduced 2.7-fold in cells grown on a glucose/xylose mixture compared with those grown solely on xylose, suggesting that there is a regulatory mechanism of xylose in L. brevis that is not stringently controlled [45].…”
Section: Production Of Value-added Chemicals and Fuels From Sugar Mixtumentioning
confidence: 99%